Clinical Significance of Raynaud Phenomenon in Systemic Lupus Erythematosus. Issue 2 (March 2022) - Barbacki, Ariane; Rached-d'Astous, Nour; Pineau, Christian A.; Vinet, Evelyne; Grenier, Louis-Pierre; Kalache, Fares; Fallavollita, Sabrina; Lukusa, Luck; Bernatsky, Sasha
Abstract : Objective: There are limited reports of the clinical significance of Raynaud phenomenon (RP) in systemic lupus erythematosus (SLE), with some suggesting RP is associated with less severe lupus. Since most prior studies were small and/or focused on a specific race/ethnic demographic, it is unclear if those results are generalizable. We evaluated whether RP was associated with demographic and clinical factors in a large multiethnic SLE cohort. Methods: We studied Montreal General Hospital SLE cohort patients who are followed with standardized annual assessments. We included patients with at least 1 visit across 2011–2018 and assessed demographic and clinical variables (using the 1997 American College of Rheumatology criteria and the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index) at their first visit. We present multivariate logistics regression analyses of cross-sectional associations between these variables and RP in SLE. Results: Of 489 SLE patients, most were female (n = 445, 91%). Mean age at SLE diagnosis was 31.5 (standard deviation, 13.5) years, and 169 (34.6%) had RP. In our fully adjusted model, female sex (odds ratio [OR], 2.43; 95% confidence interval [CI], 1.07–6.03), White race/ethnicity (OR, 1.85; 95% CI, 1.10–3.17), neurological/neuropsychiatric manifestations (OR, 1.98; 95% CI, 1.10–3.56), and anti-RNP antibodies (OR, 3.03; 95% CI, 1.73–5.38) were positively associated with RP, whereas hemolytic anemia and cellular casts were negatively associated. Conclusions/Discussion: Over one third of our large multiethnic North American SLE cohort had RP. This study confirmed associations between RP and a specific SLE phenotype.